2016
DOI: 10.1038/ncomms12429
|View full text |Cite
|
Sign up to set email alerts
|

Circular non-coding RNA ANRIL modulates ribosomal RNA maturation and atherosclerosis in humans

Abstract: Circular RNAs (circRNAs) are broadly expressed in eukaryotic cells, but their molecular mechanism in human disease remains obscure. Here we show that circular antisense non-coding RNA in the INK4 locus (circANRIL), which is transcribed at a locus of atherosclerotic cardiovascular disease on chromosome 9p21, confers atheroprotection by controlling ribosomal RNA (rRNA) maturation and modulating pathways of atherogenesis. CircANRIL binds to pescadillo homologue 1 (PES1), an essential 60S-preribosomal assembly fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
797
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 909 publications
(851 citation statements)
references
References 72 publications
18
797
4
6
Order By: Relevance
“…cANRIL, which serves as a factor in atherosclerotic cardiovascular disease and is located on chromosome 9p21, induces cell apoptosis, inhibits cell proliferation and reduces atheroprotective effects [13]. Moreover, elevated cANRIL expression increased EC apoptosis in the coronary arteries of rats, but reduced cANRIL expression resulted in an opposite trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cANRIL, which serves as a factor in atherosclerotic cardiovascular disease and is located on chromosome 9p21, induces cell apoptosis, inhibits cell proliferation and reduces atheroprotective effects [13]. Moreover, elevated cANRIL expression increased EC apoptosis in the coronary arteries of rats, but reduced cANRIL expression resulted in an opposite trend.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA ANRIL participates in the replication of the genetic risk locus for coronary artery disease (CAD), and it is independently correlated with several forms of immune-mediated, metabolic disorders and coronary heart disease [11, 12]. Previous work has demonstrated that the lncRNA ANRIL, which is transcribed at the cardiovascular disease risk locus on chromosome 9p21, can form RNA circles [13]. Circular RNAs (cRNAs) are a special type of a stable, diverse and conserved noncoding RNAs in mammalian cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, circRNAs appear to be expressed in tissue-and developmental-stage-specific manners, which indicates that they function in many physiological and pathophysiological processes [6,7]. Similar to miRNAs and lncRNAs, researchers have also found that circRNAs are related to many diseases, such as atherosclerosis, nervous system disorders, and a variety of cancers [8][9][10][11]. circRNAs are stable in cells because they are resistant to exonucleases; thus, circRNAs may constitute ideal biomarkers for cancer diagnosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…An example is the circular RNA ANRIL (antisense noncoding RNA in the INK4 locus), which affects atherogenesis by acting as a scaffold to prevent ribosomal RNA function. 115 Although circular RNAs can be challenging to interrogate because they are not captured by poly-based sequencing methods, their study has filled a substantial gap in mechanisms orchestrating cardiovascular disease. 116 Thus, epigenetic modification is no longer a term that is restricted to DNA/chromatin interrogation.…”
Section: Knockout Mouse Generationmentioning
confidence: 99%